Rob Flood Risk Index in Medan Belawan District - Anthoni Sumuang Siahaan; Abdiyanto; Feby Milanie (International Journal of Society and Law, 2024)
The flash flood in Belawan sub-district was caused by the entry of water from the Belawan and Deli rivers into the area when the sea water was at high tide. The inundation caused by the elevation of the land is below the level of the tide and river water enters through the drainage channel. Rob research in Belawan uses descriptive and qualitative methods. The distribution of inundation was analyzed using tidal analysis using the admiralty method which was the input to calculate the distribution of inundation using GIS. The flood risk index is calculated using the threat index and vulnerability index parameters. The results of this research show that the disaster risk index in Belawan sub-district is already at high risk with a risk index of 0.78.